Detection and preliminary characterization of CD8+T lymphocytes specific for Wilms' tumor antigen in patients with non-Hodgkin lymphoma. Issue 11 (November 2013) - Israyelyan, Anna; La Rosa, Corinna; Tsai, Weimin; Kaltcheva, Teodora; Srivastava, Tumul; Aquino, Lia; Li, Jianqiang; Kim, Young; Palmer, Joycelynne; Streja, Leanne; Senitzer, David; Zaia, John A.; et al.
Abstract Wilms' tumor antigen (WT1) is overexpressed in many different solid tumors and hematologic malignancies. However, little is known about WT1 expression or WT1-specific immune responses in patients with non-Hodgkin lymphoma (NHL). In a cross-sectional survey study, we investigated the immune recognition of WT1 by patients with NHL. Utilizing a WT1 overlapping peptide library, we discovered that a large percentage of patients with NHL of all grades maintain WT1-specific T cells. Ex vivo frequencies of these T cells measured from unfractionated samples by the CD137 activation marker assay were high in many patients (some > 1% CD8+). Using standard in vitro techniques we discovered that they were cytotoxic to WT1 peptide library-loaded T2 cells and WT1 antigen-primed autologous Epstein–Barr virus-transformed B cell lines (EBV-LCLs) and expressed interferon gamma (IFN-γ). In addition, we detected WT1 mRNA transcripts in diseased lymph node tissues of patients with NHL utilizing real-time quantitative polymerase chain reaction (RT-qPCR) technology. These results are the first example of strong T cell reactivity against WT1 in patients with NHL which also demonstrate strong cytotoxicity against peptide-loaded tumor cells. The potential for developing WT1 as a target for immunotherapy in NHL deserves further exploration.